Modular Fault Diagnosis in Fixed-Block Railway Signaling Systems - Durmus, Mustafa S.; Ustoglu, Ilker; Tsarev, Roman Y.; Schwarz, Michael (ELSEVIER, 2016)
The diagnosis of possible faults in railway signaling systems is an important issue to provide safe travel and transportation in railways. Signaling system designers have to consider the possible faults which may occur in railway field components both on the requirements preparation phase and on the development phase of the signaling system software or namely, the interlocking system. Although the diagnosis of different unobservable faults is relatively hard, especially for large scale railway fields, this complexity can he overcome by using the Discrete Event System (DES) based modular diagnosis approach which is explained in this paper. The main advantage of using such modular approach for fault diagnosis in fixed-block signaling systems is the inspection of the diagnosahility of the whole system with respect to its subsystems (railway field components). In this study, the diagnosahility of the railway field equipment and the whole system is also explained with a case study. (C) 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.
Keywords: Discrete Event Systems; Modular Fault Diagnosis; Fixed-Block Railway Signaling Systems; DISCRETE-EVENT SYSTEMS; FAILURE DIAGNOSIS; DIAGNOSABILITY; MODELS; Automation & Control Systems